Update in Pediatric Neuro-Oncology - Soumen Khatua (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
This Special Issue of Bioengineering explores topics in Pediatric Neuro-Oncology ranging from preclinical modeling to translational research and neurocognitive outcomes. The topics are as below. 1. Radiotherapy advances in pediatric brain tumors; 2. Neurofibromatosis 1 and brain tumors in children; 3. Molecular biology of pediatric gliomas and therapeutic insights; 4. Embryonal tumors of the central nervous system in children-era of targeted therapeutics; 5. Preclinical models in pediatric brain tumors-clinical relevance; 6. Molecular neuroimaging of brain tumors; 7. Palliative care for children with central nervous system malignancies; 8. Neurocognitive and psychosocial outcomes following pediatric brain tumors.